New insights into the relationship between the average nucleotide identity and the digital DNA–DNA hybridization values in the genus Amycolatopsis and Amycolatopsis cynarae sp. nov., a novel actinobacterium from the rhizosphere soil of Cynara scolymus, and proposal of Amycolatopsis niigatensis as a synonym of Amycolatopsis echigonensis based on comparative genomic analysis - Deng, Aihua; Fu, Li; Mo, Ping; Zheng, Yaxi; Tang, Ting; Gao, Jian (Frontiers in Microbiology, 2024)
At present, it is widely believed that 95-96 % ANI (average nucleotide identity) value is equivalent to 70 % dDDH (digital DNA-DNA hybridization) value in the prokaryotic taxonomy. However, in the present work, comparative genome analysis of 29 pairs of Amycolatopsis type strains revealed that a 70 % dDDH value did not correspond to a 95-96 % ANIm (average nucleotide identity based on MuMmer ultra-rapid aligning tool) but approximately corresponded to a 96.6 % ANIm value in the genus Amycolatopsis. Based on this corresponding relationship, phenotypic and chemotaxonomical characteristics, as well as phylogenetic analysis, an actinobacterial strain HUAS 11-8 T , isolated from the rhizosphere soil of Cynara scolymus, was